Genotyping the world collection of oat by microsatellite markers (Experimental biology, 2016)
Oat is one of the most important food and feed crops in the World. Currently the world area under the oat is less than10 million hectares and down from 13 million in 2001. Kazakhstan is one of the major oat growing countries and in 2014 the harvesting area was about 200 thousand hectares, which provided production for 226 thousand tons. In order to maintain oat supply on the World market it is required to increase efficiency of breeding projects, including based on wide use of available genetic resources. In addition, effective DNA markers are necessary for successful genetic discrimination of accessions and commercial cultivars, and for protection of intellectual rights of breeders.Therefore, the collection of oat Avena sativa L. and Аvena byzantina c. Koch.consisting from 163 accessions from Kazakhstan, Europe and America, has been studied by using polymorphic DNA microsatellite markers. In total, out of screened 29 markers, 19 markers were found to be polymorphic ones for this collection. Genetic variability of the collection was studied using PopGeneandGenAlEx 6.5 software packages. In general 86 alleles were identified for analyzed markers, which suggested 4.5 average alleles per locus and 2.6 average effective alleles. Number of alleles was varied from 2 (AM25) to 8 (AM3). Genetic indexes of Shannon and Nei were calculated both for the entire population and separate regions. Calculated values for these indexes for the entire population were 1,002 and 0,532, respectively. Most genetic variability by for Nei(0.525±0,047 и 0.521±0,052)and PIC (0.4783±0.036 и 0.4702±0.043)indexes were found for Kazakhstan and East Europe, respectively. Most informative DNA microsatellite marker was MAMA-6 (0.782), followed by MAMA-11 (0.698) and AM-1 (0.666). Phylogenetic analysis of all 163 accessions was performed by using Neighbor Joining method in MEGA 6 program. The grouping of the accessions allowed of identifying 11 separate clusters. Most of studied accessions from Kazakhstan were allocated in clusters I, III, and IV. The principal coordinate analysis (PCoA) was successfully applied to differentiate the groups of oat within studied collection. The total sum of first two coordinates in PCoA was 71.33%. It was found that North American and European accessions are genetically close to each other and far from distinct groups in Kazakhstan and South America.Obtained results could be effectively used in genotyping of commercial cultivars, in protection of intellectual rights of breeders, and for improving of oat adaptation and productivity in different regions of Kazakhstan.
Keywords: oat; world collection; genetic diversity; DNA markers